Controlled growth of NiCo2O4 nanorods and ultrathin nanosheets on carbon nanofibers for high-performance supercapacitors - Zhang, Genqiang (2013)
Two one-dimensional hierarchical hybrid nanostructures composed of NiCo2O4 nanorods and ultrathin nanosheets on carbon nanofibers (CNFs) are controllably synthesized through facile solution methods combined with a simple thermal treatment. The structure of NiCo2O4 can be easily controlled to be nanorods or nanosheets by using different additives in the synthesis. These two different nanostructures are evaluated as electrodes for high performance supercapacitors, in view of their apparent advantages, such as high electroactive surface area, ultrathin and porous features, robust mechanical strength, shorter ion and electron transport path. Their electrochemical performance is systematically studied, and both of these two hierarchical hybrid nanostructures exhibit high capacitance and excellent cycling stability. The remarkable electrochemical performance will undoubtedly make these hybrid structures attractive for high-performance supercapacitors with high power and energy densities.